2021
DOI: 10.1016/j.bspc.2021.102901
|View full text |Cite
|
Sign up to set email alerts
|

Dense GAN and multi-layer attention based lesion segmentation method for COVID-19 CT images

Abstract: As the COVID-19 virus spreads around the world, testing and screening of patients have become a headache for governments. With the accumulation of clinical diagnostic data, the imaging big data features of COVID-19 are gradually clear, and CT imaging diagnosis results become more important. To obtain clear lesion information from the CT images of patients' lungs is helpful for doctors to adopt effective medical methods, and at the same time, is helpful to screen the patients with real infection. Deep learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…As the diagnosis of COVID-19 using medical imaging has been a priority since the pandemic started, 39 (68%) of 57 studies reported the diagnosis of COVID-19 as the main focus of their work [ 19 - 21 , 23 - 33 , 35 - 37 , 39 , 41 , 42 , 44 , 46 , 50 , 52 , 53 , 55 , 56 , 58 - 60 , 63 - 69 , 71 , 72 ]. In addition, 9 (16%) studies reported data augmentation as the main task addressed in the work [ 18 , 43 , 45 , 49 , 54 , 61 , 62 ], 1 (2%) study reported prognosis of COVID-19 [ 22 ], 3 (5%) studies reported segmentation of lungs [ 34 , 51 , 57 ], and 1 (2%) study reported diagnosis of multiple lung diseases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the diagnosis of COVID-19 using medical imaging has been a priority since the pandemic started, 39 (68%) of 57 studies reported the diagnosis of COVID-19 as the main focus of their work [ 19 - 21 , 23 - 33 , 35 - 37 , 39 , 41 , 42 , 44 , 46 , 50 , 52 , 53 , 55 , 56 , 58 - 60 , 63 - 69 , 71 , 72 ]. In addition, 9 (16%) studies reported data augmentation as the main task addressed in the work [ 18 , 43 , 45 , 49 , 54 , 61 , 62 ], 1 (2%) study reported prognosis of COVID-19 [ 22 ], 3 (5%) studies reported segmentation of lungs [ 34 , 51 , 57 ], and 1 (2%) study reported diagnosis of multiple lung diseases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 57 studies, only 10 (18%) [ 18 , 19 , 26 , 27 , 30 , 34 , 43 , 61 - 73 ] reported changes to the architecture of the GAN they were using. In the rest of the studies, no major changes were reported to the architecture of the GAN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of data namely synthetic data and limited unlabeled CT images of COVID-19 were used to train this network. Authors in [26] have coped with this issue differently by using an improved dense generative adversarial network (GAN) to expand the existing dataset of COVID-19 images. However, it remains very challenging to achieve accurate segmentation of COVID-19 for several reasons.…”
Section: Related Workmentioning
confidence: 99%
“…Among several generative models, Generative Adversarial Networks (GANs) [15] have gained the attention of medical image processing researchers. Recently, GANs were used in medical image (MI) generation [16,17], medical image editing in latent space [18], MI segmentation [19], and MI classification [20], because of their better performance among all generative models. A typical GAN consists of a generator (G) and a discriminator (D) network.…”
Section: Introductionmentioning
confidence: 99%